University distance learning during Covid-19 pandemic - Abdul Rahman, Shukran (IslamiCity, 2020)
Like other sectors, the education system, including at higher education level, has also been severely affected when the Covid-19 pandemic began. A number of measures have been put in place by higher learning institutions in order to mitigate its impacts. The measures are informed by a number of fundamentals, especially on the principles that health and safety must take precedence over other matters. Covid-19 is an acute and highly contagious viral disease, transmissible through human interactions, necessitating the formulation of judicious interventions to eliminate or slow the outbreak. The need to prevent COVID-19 infections among university community warrants universities’ management to be mindful of their decisions, hence have come up with necessary guidelines to facilitate and regulate their activities, including the teaching and learning processes.